Red cell distribution width and mortality in pediatric sepsis - Trina Devina; Munar Lubis; Erna Mutiara; Gema Nazri Yanni; Rina Amalia C. Saragih; Yunnie Trisnawati; Aridamuriany Dwiputri Lubis; Putri Amelia (Indonesian Pediatric Society, 2016)
Background Red cell distribution width (RDW) is a hematological parameter routinely obtained as part of the complete blood count. Recently, RDW has emerged as a potential independent predictor of clinical outcomes in adults with sepsis. However, RDW as a mortality predictor in pediatric populations has not been well established.Objective To determine the relationship between RDW value and mortality outcomes in pediatric sepsis patients.Methods We performed a cross-sectional study of 40 consecutive pediatric patients with sepsis admitted to the PICU from December 2013 to March 2014. All patients’ RDW were collected within 24 hours of sepsis diagnosis. We determined the association between RDW and hemoglobin (Hb) using Spearman’s correlation. The RDW values of 11.5-14.5% were considered to be normal while those > 14.5% were considered to be elevated. We compared mortality and PICU length of stay (LoS) between the normal and elevated RDW groups using Chi-square and Mann-Whitney tests.Results The median age of patients was 34 months (range 2 months to 17 years). There were 28 (70%) male subjects. Subjects’ median RDW was 14.8% (range 11.2-27.8%) and was not correlated with Hb (r=0.056; P=0.73). Mortality rates in the normal and elevated RDW groups were 40% and 45%, respectively. There were no significant associations between RDW group and mortality (P=0.749) or PICU LoS (P=0.350).Conclusion Unlike in adults, RDW values are not correlated with mortality in pediatric sepsis patients.